Recent advances of non‐fullerene organic solar cells: From materials and morphology to devices and applications - Zhang, Ying; Lang, Yongwen; Li, Gang (EcoMat (Beijing, China), 2023)
The innovation of non‐fullerene acceptors (NFAs) enables the rapid progress of organic solar cells (OSCs) in power conversion efficiencies to over 19%, endowing OSCs with great potential toward real‐world application. In this critical review, we outline the recent advances of NFA‐based OSCs ‐ from ITIC‐ to Y6‐family, to exemplify the structure–performance correlations, and cover from material chemistry to nanomorphology controlling. In addition, we point out the possible degradation mechanisms behind the NFA‐based devices and strategies for mitigating the stability issues. With OSC efficiencies approaching 20% benchmark, increasing attention has been built‐up toward the technology's applications. Therefore, we describe the opportunities and challenges in the promising applications, mainly on semitransparent and flexible OSCs for commercial photovoltaics. Finally, we provide a summary and perspective to point out the primary challenges the OSC technology is facing toward commercialization. Non‐fullerene organic solar cells (NFA‐OSCs) have seen massive progress in power conversion efficiencies surpassing 19%, benefiting from material innovation and device engineering. Moreover, NFA‐OSCs show great potential for promising applications, such as semitransparent and flexible photovoltaic technology. This review outlines the latest progress of NFA‐OSCs, with a focus on Y‐series, NFAs covering from material and morphology to devices and applications.